2009
DOI: 10.1007/s10750-009-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of genetic differentiation in Brachionus calyciflorus species complex collected from East China in summer

Abstract: In this study, the mtDNA COI genes of 124 individuals in Brachionus calyciflorus complex were sequenced and analyzed. Overall, 84 mtDNA haplotypes were defined, and were split into three clades by the phylogenetic trees. The divergences of COI gene sequence among the three clades ranged from 11.4 to 22.5%, indicating the occurrence of three cryptic species (cryptic species 1, cryptic species 2, and cryptic species 3). Within cryptic species 3, a remarkable degree of differentiation (F st = 0.0947) might be att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 73 publications
4
15
0
1
Order By: Relevance
“…2007). Similarly, in an earlier study, we also found a remarkable genetic differentiation in space in the rotifer B. calyciflorus (Xiang et al. 2010).…”
Section: Introductionsupporting
confidence: 89%
“…2007). Similarly, in an earlier study, we also found a remarkable genetic differentiation in space in the rotifer B. calyciflorus (Xiang et al. 2010).…”
Section: Introductionsupporting
confidence: 89%
“…It is known that COI sequence divergences ranged from 7.2% to 26.8% and from 22.8% to 25.6% among B. calyciflorus and B. plicatilis sibling species, respectively (Derry et al, 2003;Gilbert and Walsh, 2005;Li et al, 2008;Xiang et al, 2010Xiang et al, , 2011. In this study, COI sequence divergence ranged from 11.8% to 17.8% between the two clades, indicating that they are two sibling species of the B. calyciflorus complex.…”
Section: Taxonomic Identification and Toxicant Sensitivity Of The Spesupporting
confidence: 47%
“…Due to their cosmopolitan distribution, shorter generation time, smaller body size (about 150 μm), rapid frequency of reproduction, professional endorsement of toxicological evaluations and feasibility of cultures in the laboratory, rotifers, especially Brachionus calyciflorus and Brachionus plicatilis, are frequently used for aquatic ecotoxicology (Snell and Janssen, 1995). In the past two decades, accumulating evidence has shown that many rotifer species, such as B. plicatilis and B. calyciflorus, traditionally categorized as cosmopolitan, are now recognized as cryptic species complexes (e.g., Ciros-Pérez et al, 2001;Derry et al, 2003;Gilbert and Walsh, 2005;Gómez et al, 1995Gómez et al, , 2002aGómez et al, , 2002bLi et al, 2008;Xiang et al, 2010). Toxicity tests have shown that four sibling species in B. plicatilis species complex displayed different sensitivities to Corexit 9500A s , propylene glycol and Macondo oil (Rico-Martínez et al, 2013), but the differences in the sensitivities in life table demographic parameters between sibling species in B. plicatilis or B. calyciflorus species complex to fly ash effluent remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, facilitated through technical advances such as PCR and direct DNA sequencing, many phylogenetic, phylogeographic and population genetic studies discovered many cryptic lineages, which were genetically divergent, but morphologically similar (Pfenninger and Schwenk, 2007). Cryptic species are distributed among major metazoan taxa including rotifers such as Brachionus plicatilis, Keratella cochlearis, Brachionus calyciflorus, Epiphanes senta, Rotaria rotatoria and some categories of Adineta Go´mez and Snell, 1996; Ciros-Pe´rez et al, 2001a; Go´mez et al, 2002;Derry et al, 2003;Gilbert and Walsh, 2005;Cheng et al, 2008;Li et al, 2008;Fontaneto et al, 2009Fontaneto et al, , 2011Li et al, 2010;Xiang et al, 2010Xiang et al, , 2011aXiang et al, , 2011b. The research of cryptic species, especially rotifer cryptic species, not only are needed for studying species diversity, but also help us understand the mechanisms of species coexistence, niche differentiation and speciation.…”
Section: Introductionmentioning
confidence: 99%